2014
DOI: 10.1016/j.bmcl.2014.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 3,6-disubstituted dihydropyrones as inhibitors of human lactate dehydrogenase

Abstract: A series of 3,6-disubstituted dihydropyrones were identified as inhibitors of human lactate dehydrogenase (LDH)-A. Structure activity relationships were explored and a series of 6,6-spiro analogs led to improvements in LDHA potency (IC50 <350 nM). An X-ray crystal structure of an improved compound bound to human LDHA was obtained and it illustrated additional opportunities to enhance the potency of these compounds, resulting in the identification of 51 (IC50=30 nM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…To build up this database, small molecules for which an LDH inhibition assay was reported in the literature were analyzed. About 200 compounds were identified as LDH inhibitors able to interact with the open conformation of the enzyme in the presence of NADH, and 93 compounds showing an IC 50 lower than 15 µM were selected as active LDH inhibitors [16,18,19,20,21]. As regards the choice of decoys, we downloaded all of the decoys included in the Maximum Unbiased Validation datasets reported by Rohrer and Baumann [22].…”
Section: Resultsmentioning
confidence: 99%
“…To build up this database, small molecules for which an LDH inhibition assay was reported in the literature were analyzed. About 200 compounds were identified as LDH inhibitors able to interact with the open conformation of the enzyme in the presence of NADH, and 93 compounds showing an IC 50 lower than 15 µM were selected as active LDH inhibitors [16,18,19,20,21]. As regards the choice of decoys, we downloaded all of the decoys included in the Maximum Unbiased Validation datasets reported by Rohrer and Baumann [22].…”
Section: Resultsmentioning
confidence: 99%
“…Several classes of inhibitors of LDHA have been described and a wealth of structural information and binding affinity data are available 6277. The set of compounds ( 1–11 ) studied include seven from high-throughput screening (HTS) of the Genentech/Roche corporate compound collection;66,68,69,71,72,78 two small, negatively charged compounds;73 and three compounds sharing malonate as a common substructure originating from AstraZeneca's fragment screening approach (Table 2, Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…In parallel to the SAR studies reported above, the series of compounds was expanded by synthesizing analogues bearing modifications on the central core [ 9 ]. The results showed that a dihydropyrone scaffold could endow the ligands with slightly better apparent cell permeability and slightly lower human plasma protein binding without negatively affecting their inhibitory activity.…”
Section: X-ray Structure Analysesmentioning
confidence: 99%
“…Silencing by sh RNA or chemical inhibition of h LDH5 induces a decrease of cell proliferation and migration [ 2 , 3 , 4 , 5 , 6 ]. In the last decade, h LDH5 has gained a considerable attention as an attractive and potentially safe therapeutic target, and many inhibitors either synthetic [ 7 , 8 , 9 ] or isolated from natural sources [ 10 , 11 ] have been reported in literature. Nevertheless, inhibition of this enzyme remains a challenging goal, since the active site of h LDH5 comprises both a substrate binding pocket, which usually hosts the small polar structure of the substrate pyruvate, and a cofactor binding site, where NADH, which is more extended than the substrate and is composed of lipophilic as well as polar portions, is located.…”
Section: Introductionmentioning
confidence: 99%